Good Carry, Bad Carry - Bekaert, Geert; Panayotov, George (Journal of Financial and Quantitative Analysis, 2020)
We distinguish between "good" and "bad" carry trades constructed from G-10 currencies. The good trades exhibit higher Sharpe ratios and sometimes positive return skewness, in contrast to the bad trades that have both substantially lower Sharpe ratios and highly negative return skewness. Surprisingly, good trades do not involve the most typical carry currencies like the Australian dollar and Japanese yen. The distinction between good and bad carry trades significantly alters our understanding of currency carry trade returns, and invalidates, for example, explanations invoking return skewness and crash risk.